Antibacterial Effect of Potassium Tetraborate Tetrahydrate against Soft Rot Disease Agent Pectobacterium carotovorum in Tomato - Ahmed, Firas A.; Arif, Mohammad; Alvarez, Anne M. (Frontiers in Microbiology, 2017)
Soft rot caused by Pectobacterium carotovorum is one of most common bacterial diseases occurring on fruits and vegetables worldwide, yet consumer-acceptable options for postharvest disease management are still insufficient. We evaluated the effect of potassium tetraborate tetrahydrate (B4K2O7.4H2O) (PTB) on growth of P. carotovorum using strain BA17 as a representative of high virulence. Complete inhibition of bacterial growth was achieved by treatment with PTB at 100 mM both at pH 9.2 and after adjustment to pH 7.0. Bactericidal activity was quantified and validated by counting fluorescently labelled live and dead bacterial cells using flow cytometry, and reconfirmed using qPCR with high affinity photoreactive DNA binding dye propidium monoazide (PMA). The results of flow cytometry, qPCR, and culturing confirmed that bacterial cells were killed following exposure to PTB at 100 mM. Bacterial cell membranes were damaged following a five-minute treatment and extrusion of cytoplasmic material from bacterial cells was observed using transmission electronic microscopy. Soft rot incidence on inoculated tomato fruit was significantly reduced by dipping infected fruits in PTB at 100 mM for 5 min and no lesions developed following a 10-minute treatment. PTB does not pose a hazard to human health and is an effective alternative to other bactericides and antibiotics for controlling soft rot disease of tomato caused by P. carotovorum